Underpricing Emisi Saham Perdana: Suatu Tinjauan Kritis - Muniya Alteza (Jurnal Manajemen Maranatha, 2010)
A firm needs enough capital to push up its growth. There are many sources of fund, such as retained earnings, debt and equity. The firm should choose one which can maximize the value of the firm, identical with minimize the weighted average cost of capital. To use equity as its funding, the first step must be taken by the firm is offering stock in the primary market, this called Initial Public Offering. A commin phenomena happened in the IPOs in underpricing. This paper first tried to review the definition and process of IPOs and also explore many theories to explain underpricing. Last, it will review some empirical evidence from many researches.Keywords: IPO, underpricing, asymmetric information, aftermarket liquidity, market climate, signaling, underwritter